Evaluation of Water Purification Potentials of Moringa Seed (Moringa oleifera) In Jalingo Local Government Area of Taraba State - Yusuf, Obadiah Saveni; Abershi, Ajiduku Leyoa; Chuanu, Solomon; Bappa, Lipana Dorcas; Ngabea, Nasiru Audu; Mafe, Alice Njolke; Bando, David Christopher; Peter, Danladi Mbosire; Umaru, Isaac John (African Journal of Clinical Medicine and Pharmacy Research, 2024)
Agricultural, Domestic and Industrial activities are all human activities that led to squalid of environment, mostly water pollution. Water is needed for every daily activities and conventional methods of treating wastewater such as the use of chlorine and other is detrimental to human health. Hence, there is need for a greener sustainable alternative of wastewater treatment such as biological method. This study focused on developing an efficient and cost-effective procedure for using Moringa oleifera seeds to produce natural coagulant for use in drinking water treatment. The study investigates processing Moringa oleifera seeds to concentrate the bio-active constituents which have coagulation activity. It is generally accepted that Moringa works as a coagulant due to positively charged, water-soluble proteins, which bind with negatively charged particles (silt, clay, bacteria, toxins, etc) thereby allowing the resulting “flocs” to settle to the bottom and then be removed by filtration. The turbidity removal was about 83-100% using two processed Moringa oleifera seeds to treat an undrinkable well water having 6 Nephelometric Turbidity Units (NTU). The product satisfies WHO standards for portable water and minimizes the cost of water treatment and therefore it is recommended as an efficient and effective treatment for drinking water especially for the rural communities where there is poor access to potable water.